2003
DOI: 10.1046/j.1525-1446.2003.20503.x
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Characteristics of Comprehensive Prenatal Case Management Programs

Abstract: The purpose of this study was to examine comprehensive prenatal case management programs in terms of organizational, program, and process characteristics. Data from 66 program surveys of government agencies were used. Organizational capacity was measured as extent of organizational change and extent of interagency agreements. Program data included age and size of the program, reasons for having case management, and funding diversity. Process data were eight types of interventions. The most highly rated reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Our analyses of correlates of nurse case manager practice activities indicate that the nurse case Our findings increase understanding of the frequency of case manager practice activities reported by Tahan (1999) and Issel et al (2003) by making a distinction between client service and bureaucratic activities. We found that the most frequently performed activity by WHN nurse case managers was a bureaucratic task the other analyses did not distinguish-documenting services.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our analyses of correlates of nurse case manager practice activities indicate that the nurse case Our findings increase understanding of the frequency of case manager practice activities reported by Tahan (1999) and Issel et al (2003) by making a distinction between client service and bureaucratic activities. We found that the most frequently performed activity by WHN nurse case managers was a bureaucratic task the other analyses did not distinguish-documenting services.…”
Section: Discussionsupporting
confidence: 58%
“…Other relevant organizational factors include client caseload size and required documentation of activities, as well as space, staff mix, availability of interpreters, and practice standards (Issel, 1997;Issel & Anderson, 2001;Issel et al, 2003). For example, Issel et al (2003) found that case managers working in larger programs spent significantly less time providing emotional support and more time on education than those working in smaller programs.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…The case management system of care supported women's restoration by providing referrals and guidance through stressful issues of housing, income, and education. Although challenging to measure direct benefits, case management strategies have shown success in improving maternal and infant health outcomes for socially vulnerable women [38]. The intangible benefits of emotional support, coaching and encouragement by a personal provider may be especially helpful in post-disaster recovery [39].…”
Section: Discussionmentioning
confidence: 99%
“…A community-based, health-related service provided to medically or socially high-risk pregnant women for the purpose of improving birth and early infancy outcomes is prenatal case management (PCM), sometimes offered through home visiting [1]. Historically, local health departments in many states provided PCM as a Medicaid reimbursable service.…”
Section: Introductionmentioning
confidence: 99%
“…This study sought to answer two research questions: [1] what differences exist between adolescent and adult populations in the breadth of health and social problems addressed by PCM programs, and [2] what variation exists in the types of interventions used by PCM case managers to address adolescent and adult problems.…”
Section: Introductionmentioning
confidence: 99%